The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1574-6941.12306
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition of divergent soil habitats in a polar desert

Abstract: Edaphic factors such as pH, organic matter, and salinity are often the most significant drivers of diversity patterns in soil bacterial communities. Desert ecosystems in particular are model locations for examining such relationships as food web complexity is low and the soil environment is biogeochemically heterogeneous. Here, we present the findings from a 16S rRNA gene sequencing approach used to observe the differences in diversity and community composition among three divergent soil habitats of the McMurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Furthermore, pH was recently proposed to be the best predictor of microbial diversity at the phylum level (Geyer et al, 2014), which is consistent with a recent study of the presence of Acidobacteria along an elevational gradient (Zhang et al, 2014). Acidobacteria is one of the most dominant soil genera, which could reflect its metabolic plasticity.…”
Section: Soil Phsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, pH was recently proposed to be the best predictor of microbial diversity at the phylum level (Geyer et al, 2014), which is consistent with a recent study of the presence of Acidobacteria along an elevational gradient (Zhang et al, 2014). Acidobacteria is one of the most dominant soil genera, which could reflect its metabolic plasticity.…”
Section: Soil Phsupporting
confidence: 85%
“…In an analysis of soil bacteria diversity, Zhang et al (2013) found that Proteobacteria was the dominant group and was significantly associated with the amount of soil moisture. Geyer et al (2014) investigated the association between the type of soil and bacterial diversity in Polar desert soils, and also found that moisture content was closely related to the abundance of several bacterial genera.…”
Section: Structure and Soil Typementioning
confidence: 99%
“…Nitrospira are the only known thermophilic NOB; whereas, Ca. Nitrotoga, Nitrospina, and Nitrospira have been detected in polar settings [104][105][106]. Overall, Ca.…”
Section: Environmental Distributionmentioning
confidence: 94%
“…Model soils help to establish causative relationships that may be obscured in other systems by confounding variables. Our earlier work from this system documented an asymptote in bacterial diversity along a naturally occurring soil productivity gradient (Geyer et al ., ; Geyer et al ., ). The objectives of the present study are to (i) confirm earlier observations with a manipulative experiment and (ii) induce a broader resource gradient than natural field conditions provide in order to capture the full potential response profile of bacterial diversity.…”
Section: Introductionmentioning
confidence: 97%